Effect of Maternal Body Mass Index on the Efficacy of Antenatal Betamethasone Administration in Neonatal Outcomes - Masoumeh Mirzamoradi; Soraya Saleh Gargari; Parichehr Pooransari; Mahboobeh Shirazi; Maryam Ahmadyan; Zahra Naeiji; Nayereh Rahmati; Taraneh Arbabzadeh; Neda Ahmadyan (Mashhad University of Medical Sciences, 2022)
Background: Maternal obesity affects the health of infants and pregnancy outcomes. Few studies, to the best of our knowledge, have assessed the relationship between maternal body mass index (BMI) at antenatal corticosteroid therapy (ACS) and the frequency of preterm adverse outcomes results of which were discrepant. The present study aimed to investigate the prevalence of several neonatal morbidities based on maternal BMI among pregnant women who received a single course of ACS. Methods: The present retrospective study was conducted on pregnant women referred to Mahdieh Hospital in Tehran, Iran between 2021 and 2022. Medical records of pregnant women were included who received a single course of betamethasone with the risk of preterm birth. The mothers were divided into three groups in terms of weight after checking the inclusion criteria. Clinical characteristics and neonatal outcomes were collected and analyzed using soft statistics. Results: A total of 610 medical records (30.49%: normal weight, 57.54%: overweight, and 11.98%: obese) were included. Also, the cesarean section rate in overweight and obese cases was significantly higher than that of the normal BMI group (P<0.05). No significant relationship was observed between maternal BMI and neonatal mortality or morbidity (P> 0.05). Conclusion: BMI was more associated with increased cesarean section rate in overweight and obese groups. However, no significant relationship was observed between maternal BMI and neonatal outcomes. This result suggests that BMI fails to affect the efficacy of betamethasone.